The fiscal residence of natural persons as it applies to South Africans working abroad: A study of South Africa, United States of America, United Kingdom and Australia and agreements for the avoidance of double taxation - Warden, Douglas C S (Department of Commercial Law, 2023)
For both natural and non-natural persons the basis of South African income tax changed for years of assessment commencing on or after 1 January 2001. Prior to 2001 South Africa's income tax regime was based on the source principle. Taking the cue from the Katz Commission Reports, Minister of Finance Trevor Manuel introduced the residence basis of taxation in his 2000 budget speech, thus ensuring that South African residents (as, defined in the Income Tax Act 58 of 1962 (as amended)(the 'Act')) became taxable on their worldwide income. This paper explores the South African ('SA') residence definition as well as those of the United States of America ('US'), United Kingdom ('UK') and Australia, taking cognisance of the effect of South African Agreements for the Avoidance of Double Taxation ('DTAs') with these countries (a summary table of the different treatments is presented in Appendix A). The scope of the paper has been limited to South African individuals only and specifically excludes non-natural persons and non-residents (for South African tax purposes). The choice of the countries selected was based largely on the (be it perceived or actual) popularity as destinations for South African short- and long-term contract (or other) workers. These countries are also major trading partners and have well developed economies and tax regimes, which provides for useful discussion. The scope of this paper has been limited to exclude a full discussion on the implications of capital gains tax. However, a short discussion on the change of a South African individual's residency status is pertinent to the paper and has been included at the end of the paper.